Nilai-nilai dan Parameter Demokrasi dalam Kehidupan Masyarakat Bali - I Wayan Gede Suacana (Universitas Udayana, 2015)
Balinese culture has a lot of potential values of democracywhich up till now still become the basis in the society’s life. Toexplore this potentiality, this study is trying to explain howthe manifestation of the normative democratic values andthe empirical democracy are implemented in society of Bali.This writing is based on the research which used qualitativemethod that covered the collection of primary and secondarydata, theories of analyzing data, analysis and interpretationof already selected data. Writing and constructing the wholeresult of this research were also done in this study.Based on the result of this research, it was found that themanifestation of the normative democratic values show thatthere were respects for the individual rights, obedience politicalfatsoen, the spirit of cooperation, rotation of the autority andperiodical succesion, equality and respect for citizen’rights,tolerance in dessent, transparency and accountabilty of theauthority holders, and participation in public policy.Meanwhile, the empirical manifestation of thedemocracy which is reflected in many aspects of Balinese lifegreatly affects how the describe the concept of democracy asthe basis of the strength and independence of the transitionof the democracy happening nowdays. The application of thevalues and the parameter of the democracy also influence theform and the characteristic of the relation between Balinesesociety and the government as part of the institution.